Cusanus on the Doctrine of the Image of God: Human Mind as the Living Image, Equality and Identity in Difference - İhsan Berk Özcangiller (Ankara Üniversitesi İlahiyat Fakültesi Dergisi)
The relationship between God and humans has been a matter of controversy that interests both philosophers and theologians alike. Establishing a relationship between the infinite God and finite human is particularly challenging if one admits that God and humans are substantially different from each other. The biblical doctrine of the image of God responds to this challenge by stating that the relationship between God and humans is a kind of likeness or assimilation. This doctrine does not only establish the nature of the relationship between God and humans but also views both God's and humans’ nature in a particular way and determines humans’ purpose and distinguishing feature in relation to God. While there is a very long and extensive tradition focusing on identifying the similarities and differences between God and humans to determine the precise relationship between them in light of this doctrine, this paper will focus on Nicolaus Cusanus' original contribution to this long-lasting debate. In order to emphasize Cusanus' differences from his predecessors, I will present a general historical background of the doctrine of the image of God. In particular, I will point out the main tenets of Greek and Latin patristic traditions by identifying their differences and shared assumptions. Additionally, I will briefly present Augustine's dynamic account of the image of God, which holds an important place both in the discussion among these traditions and in the development of Cusanus' doctrine of the human mind as the living image of God. As this paper will demonstrate, Cusanus improves upon Augustine's account by allowing humans to be considered as an equal image of God, which was attributed only to Jesus by Augustine. Cusanus thinks that the human mind can be considered equal to the divine mind because it demonstrates characteristics of free creative activity and being the cause of something from nothing in cognition. Moreover, to elaborate Cusanus' original contribution to this debate, I will explain how the human mind reflects the triadic nature of divine mind in itself through its cognitive activity by giving a detailed account of Cusanus’ theory of cognition as assimilation. This explanation will also show how reading Cusanus' theory of cognition as assimilation alongside the concept of equality exhibits the principle of ‘identity in difference’ in both the nature of the human mind and its relationship with the divine mind.